Pengaruh Variasi Sudut Keluar Impeler Terhadap Performance Pompa Sentrifugal - Siregar, Munawar Alfansury; Damanik, wawan Septiawan (Rekayasa Material, Manufaktur dan Energi, 2020)
The ability of a pump to drain or move a certain amount of fluida / fluida that comes out through the pressure side of the pump in units of time volume is also called the capacity of a pump. Meanwhile, the pump head is the energy per unit weight that must be provided to flow the planned amount of liquid according to the pump installation conditions. A centrifugal pump is a pump that moves liquid by utilizing the centrifugal force generated by the impeller ratation. The results of data calculations and graphic analysis on the effect of variations in the impeller entry angle on the impeller with exit angle (?2) = 250,standard pump impeller,and impeller with exit angle (?2) = 350 on the performance of the centrifugal pump can be concluded, namely the performance value of centrifugal pumps. The highest is the impeller with exit angle (?2) = 250 where the specific speed value produced is 192.52 rpm and the efficiency level of this impeller is 6.82%